Effect of Sintering Time on Superconducting Wire Bi-Pb-Sr-Ca-Cu-O With Dopant MgO Sheated Ag Using Powder in Tube Method - Hariyati Lubis; Agung Imaduddin; Eddy Marlianto; Pius Sebleku; Eidi Sihombing (Journal of Aceh Physics Society, 2018)
Telah dilakukan penelitian mengenai variasi waktu proses sintering pada kawat superkonduktor Bi-Pb-Sr-Ca-Cu-O dopan MgO dengan selubung Ag. Bahan-bahan yang digunakan ialah Bismuth (III) Oksida, Timbal (IV) Oksida, Strontium Carbonate, Calcium Carbonate, Copper (II) Oksida dan Magnesium Oksida dengan tingkat kemurnian tinggi. Proses sintering dalam furnance dilakukan pada suhu konstan selama 30 jam dan 9 jam lalu didinginkan dalam tungku. Hasil karakterisasi X-Ray Diffraction dan search match v1.10, sampel kawat superkonduktor monofilamen Bi1.6Pb0.4Sr2Ca2Cu3O10+δ dan Bi1,6Pb0,4Ca1,95Mg0,05Cu3O10+δ dengan variasi waktu sintering masing-masing 30 jam dan 9 jam memiliki nilai intensitas sebesar 993,77cts dan 902,86 cts. Penambahan waktu sintering pada sampel superkonduktor mengakibatkan penurunan fraksi volume 2223 dengan masing-masing nilai fraksi volume sebesar 60% dan 59%, hal ini menunjukkan adanya impuritas berupa senyawa CuO. Parameter kisi diperoleh yaitu Orthorhombic dengan a=5,347 Å, b=5,416 Å dan c=30,67 Å. Hasil morfologi SEM menunjukkan permukaan homogenitas butir sampel terlihat cukup baik, dan terdistribusi secara acak. Pada sampel kawat superkonduktor monofilamen Bi1.6Pb0.4Sr2Ca1.95Mg0.05Cu3O10+δ dengan waktu sintering 30 jam menunjukkan Tconset=72 K dan Tczero=33 K. Sampel kawat superkonduktor monofilamen Bi1.6Pb0.4Sr2Ca1.95Mg0.05Cu3O10+δ dengan waktu sintering 9 jam menunjukkan Tconset=78 K dan Tczero=58 K. Variation of sintering time has been done in Bi-Pb-Sr-Ca-Cu-O superconducting wires dopant MgO using Ag-sheathed. The samples were prepared using highly pure powders of Bismuth (III) Oxide, Lead (IV) Oxide, Strontium Carbonate, Calcium Carbonate, Copper (II) Oxide and Magnesium Oxide. Sintered at a constant temperature for 30 h and 9 h then cooled in the furnace. The structure of the samples was studied by X-Ray Diffraction and search match v1.10. XRD patterns of Bi1.6Pb0.4Sr2Ca2Cu3O10+δ and Bi1,6Pb0,4Ca1,95Mg0,05Cu3O10+δ monofilament superconducting wires using variation of sintering time for 30 h and 9 h have intensity values of 993.77cts and 902.86 cts. The addition of sintering time to superconductor samples resulted decrease in the volume fraction of 2223 with each volume fraction value of 60% and 59% indicating of impurity phases present CuO compounds. The Orthorhombic structure with the lattice constants are calculated as a = 5,347 Å, b = 5,416 Å, and c = 30,67 Å. The surface morphology studied by SEM, show that surface homogeneity, each grain grows in random directions. For the prepared Bi1,6Pb0,4Ca1,95Mg0,05Cu3O10+δ monofilament superconducting wires sample with 30 h, the onset Tc is at 72 K and the resistivity drops to zero at 33 K. Sample of Bi1.6Pb0.4Sr2Ca1.95Mg0.05Cu3O10+δ δ monofilament superconducting wires with 9 h, the onset Tc is at 78 K and the resistivity drops to zero at 58 K. Keywords : BPSCCO superconducting wire, Sheated Ag, Dopant MgO, Sintering time DAFTAR PUSTAKAAbbas M.M., Abass L.K and Salman U., (2012), Influences of Sintering Time on the Tc of Bi2-xCuxPb0.3Sr2Ca2Cu3010+ High Temperature Superconductors, Energy Procedia 18, 215-224 Abbas, M.M., Abbas, L.K., Bahedh, H.S. 2015. Superconducting Properties of Bi2-SbxPb0,3Sr1,9Ba0,1Ca2Cu3O10+δ Compounds. Journal of Applied Science Research. 11. 22: 164-172Darsono, N., Imaduddin, A., Raju, K., Yoon, D.H., (2015), Synthesis and Characterization of Bi1.6Pb0.4Sr2Ca2Cu3O7 Superconducting Oxide by High-Energy Milling, J Supercond Nov Magn.E. Chew,. (2010), Superconducting Transformer Design And Construction, University of Canterbury, Christchurch, New Zealand. MarchHamadneh, I., Halim, S. A., dan Lee, C. K., (2006),  Characterization of Bi1.6Pb0.4Sr2Ca2Cu3Oy Ceramic Superconductor Prepared Via Coprecipitation Method at Different Sintering Time, J. Mater. Sci, 41: 5526-5530.Hermiz G.Y., Aljurani B.A., Beayaty M.A., (2014), Effect of Mn Substitution on the Superconducting Properties of Bi1.7Pb0,3Sr2Ca2-xMnxCu3O10+, International Journal Of Engineering and Advanced Technology (IJEAT). 3. 4: 213-217John R Hull, (2003), Applications of high-temperature superconductors in power technology, Reports on Progress in Physics, Volume 66, Number 11Lu, X.Y., Yi, D., Chen, H., Nagata, A. 2016. Effect of Sn, MgO and Ag2O mix-doping on the formation and superconducting properties of Bi-2223 Ag/tapes. Physics Procedia. 81: 129-132Meretliev Sh., Sadykov K.B., Berkeliev A., (2000), Doping of High Temperature Superconductors, Turk J Phy.24: 39-48Mohammed, N. H., Ramadhan A., Ali I. A., Ibrahim, I. H., dan Hassan, M. S, (2012), Optimizing the Preparation Conditions of Bi-2223 Superconducting Phase Using PbO and PbO2, Materials Sciences and Applications, 3: 224-233.Roumie, M., Marhaba, S., Awad R., Kork M., Hassan I., Mawassi R., (2014), Effect of Fe2O3 Nano-Oxide Addition on the Superconducting Properties of the (Bi,Pb)-2223 Phase, Journal of Supercond Nov Magn, 27: 143-153Serkan, A., (2008), Production of YBCO Superconductor Sample by Powder-In-Tube Method (PITM); and Effect of Cd and Ga Doping on the System, University, Department of Physics, Malatya-TurkeySharma, D., Kumar, R., Awana, V.P.S. 2013. DC and AC Susceptibility Study of Sol-Gel Synthesized Bi2Sr2CaCu2O8+x Superconductor. Ceramic International. 39:1143-1152